Eccrine angiomatous naevus revisited - Sumit Sen; Gobinda Chatterjee; Pradip K Mitra; Anusree Gangopadhyay (Wolters Kluwer Medknow Publications, 2012)
Hamartomatous, circumscribed swellings of the extremities make an interesting study. Presentations are manifold and the naevi are not always present from birth. Excessive growth of hairs leads to remarkable appearance of such swellings. A young woman presented to the dermatology department, complaining of tenderness over 4 th finger of her left hand. The defect was present for the last couple of years and was typified by visible hyperhidrosis on gentle tapping. Counseling of the affected lady made her agree for a skin biopsy. The histopathology revealed it to be of the nature of eccrine angiomatous hamartoma. Blood vessels were scarce. Eccrine ducts were plentiful without other associated anomalies. The deformity was removed by simple excision with good result.